Word and Meaning as a Problem in the Rhetorical and Miraculous Heritage of Arabs - Al-Shbeil, Abeer Obeid (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to provide a comprehensive overview of the relationship between words and meaning. Its integrative approach draws insights from various environments, involving critics, linguists, rhetoricians, and philosophers. The study explores the different paths taken in the debate between the two poles: expression and meaning. It also highlights the connection between these binary poles at the level of discourse and the relationship between language and thought. Methods: The study follows an integrative approach. It begins with an introduction that distinguishes between the functional and literary levels of discourse. It then explores the relationship between language and thought, tracing the paths taken by the issue of expression and meaning. The study presents the opinions of prominent figures in each path and discusses these viewpoints. Results: The study reveals that the duality of word and meaning has been addressed in literary and rhetorical heritage through four paths. The first path emphasizes the primacy of the word, the second emphasizes the primacy of meaning, the third emphasizes the integration and interaction of imagery and form, and the fourth emphasizes integration within the structure of the text while considering grammatical meanings. The study also indicates that the two most promising paths for exploring the duality of word and meaning are the third and fourth paths. Conclusions: The study concludes that the issue of word and meaning is deeply rooted in literary and critical heritage, engaging scholars over many centuries. There is no evidence to suggest that the presence of that issue extended over time from the beginning of the 3rd Hijri century until the 6th Hijri century, in various environments involving speakers, critics, rhetoricians, and philosophers.